Integrated Sustainability Finance Model Based on Maqāṣid Ibnu 'Āshūr – ESG: Policy Recommendations for Regulators and the Islamic Banking Industry - Siti Umi Nurbaidah; Asyari Hasan (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study proposes a conceptual model of sustainability finance that integrates the principles of maqāṣid al-sharīʿah from Ibn 'Āsyūr's perspective with the Environmental, Social, and Governance (ESG) framework, as a comprehensive value strategy in the Islamic financial system. This model is designed to address the challenge of weak integration between Islamic spiritual values and global sustainability policies, which have tended to be technocratic and symbolic. The research method uses a systematic literature review approach with the PRISMA protocol and thematic synthesis of 27 literatures from Scopus and SINTA journals, as well as official documents from the Financial Services Authority (OJK), the IMF, the BIS, and the World Bank. The result is the formulation of a three-dimensional model (normative, regulatory, practical) that recommends ESG indicators based on maqāṣid, as well as a sustainability policy framework that can be adopted by regulators, the Islamic banking industry, and academics. These findings reinforce the urgency of ESG as a long-term value strategy, aligned with the objectives of sharia and the role of humans as khalifah fil-ardh. This model also contributes to supporting the SDGs goals in a contextual and Islamic manner.